Investigation of parameters affecting throwing velocity and accuracy in handball - Neslihan Akçay; Kerem Can Yıldız; Sezer Tanrıöver; Mehmet Ali Kanı; Mustafa Şakir Akgül; Fatma Neşe Şahin (Ozlem Book Center, 2023)
Handball is a team sport in which changing direction, running fast-slowly, jumping, throwing, throwing accuracy, and tackles are at the forefront. For basic throws in the game, throwing speed and accuracy are important factors for a successful throw. In this context, the aim of this study is to evaluate the effects of body composition, isokinetic strength, handgrip strength, and static and dynamic balance parameters on throwing speed and accuracy in handball players. A total of 20 male handball players with an average age of 14.95±0.24 years and an average sports age of 4.15±0.44 years participated in the study voluntarily. Body composition, static and dynamic balance, hand grip strength, shoulder and arm rotation, throwing velocity and accuracy tests were performed on the athletes. While a negative correlation was found between body weight (r=-0.61), body mass index (r=-0.66), body muscle mass (r=-0.5), body fat mass (r=-0.58), Body fat % (r=0.61), Dominant arm muscle (r=-0.52) parameters and throwing accuracy, a positive correlation was found between dominant hand grip (r=0.59) and dominant arm shoulder internal rotation strength (r=0.59), non-dominant arm shoulder internal rotation strength parameters and throwing velocity (p<0.05). No correlation was found in the static and dynamic balance parameter. In line with the findings of the study, the static and dynamic balance parameters of the handball players did not have an effect on the throwing velocity and accuracy. However, while anthropometric characteristics such as body weight, body fat percentage and mass, and muscle mass had an effect on throwing accuracy, it can be said that hand grip strength, isokinetic shoulder internal and external rotation strength were effective on throwing velocity.